Predictors associated with treatment initiation and switch in a real‐world chronic hepatitis B population from five European countries. Issue 9 (15th December 2013) - Leblebicioglu, H.; Arama, V.; Causse, X.; Marcellin, P.; Ozaras, R.; Postawa‐Klozinska, B.; Simon, K.; Suceveanu, A. I.; Wiese, M.; Zeuzem, S.; Klauck, I.; Morais, E.; et al.
Summary In Europe, healthcare systems differ between countries and different factors may influence Chronic hepatitis B (CHB) treatment choices in different counties. This analysis from a prospective, longitudinal, non‐interventional study in five EU countries aimed to explore determinants associated with treatment initiation or switch in patients with CHB. A total of 1267 adult patients with compensated CHB in Germany, France, Poland, Romania and Turkey were prospectively followed for up to 2 years (March 2008–December 2010). Determinants of treatment initiation or switch were analysed using multivariate Cox proportional hazards regression. Median time since CHB diagnosis was 2.6 (0–37.7) years. Among 646 treatment‐naïve patients, the probability of treatment initiation during follow‐up was higher: in Germany (P = 0.0006), Poland (P < 0.0001) and Romania (P = 0.0004) compared with Turkey; in patients with alanine transaminase (ALT) 1–2 × upper limit of normal (ULN) (P = 0.0580) or >2 × ULN (P = 0.0523) compared with ALT ≤1 × ULN; and in patients with hepatitis B virus (HBV) DNA ≥2000 IU/mL (P < 0.0001) compared with HBV DNA <2000 IU/mL or undetectable. Among 567 treated patients, 87 switched treatment during follow‐up. The probability of treatment switch was higher: in France (P = 0.0029), Germany (P = 0.0078) and Poland (P = 0.0329) compared with Turkey; and in patients with HBV DNA <2000 (P < 0.0001) or ≥2000 IU/mL (P < 0.0001), compared with undetectable. Viral load and ALT level were identified as the major drivers of treatment initiation. HBV DNA level was also a significant determinant of treatment switch. Results were statistically different across EU countries.